Stress, anxiety and depressive levels among Mothers of ADHD children and their relationships with ADHD symptoms - Musa, Ramli; Shafiee, Zasmani (ASEAN Federation Of Psychiatry, 2008)
Introduction: To date, there are limited published literatures addressing behaviors of Attention Deficit and Hyperactive Disorder (ADHD) children and their parents’ psychological characteristics. It is also crucial to know the relationship between characteristics of ADHD behaviors on their parental psychological impacts. Objective: To determine the level of stress, anxiety and depressive among mothers of ADHD children compared to control group and also to determine the associations between domains of children’s behaviors (externalizing or internalizing) that gives most impact to these maternal psychological aspects. Method: This is a cross-sectional study. Seventy mothers of ADHD children who came to Child and Adolescent Clinic, Universiti Kebangsaan Malaysia Hospital completed self-rating questionnaires of Child Behavior Checklist (CBCL), Parenting Stress Index (PSI) and Hospital Anxiety and Depressive Scale (HADS). Seventy mothers of asthmatic children were recruited as a control group. Results: Mothers with ADHD children are more anxious, depressed and stressed (p<0.001). Odd ratios are 3.8, 6.4 and 6.4 respectively. ADHD children displayed difficult behaviors in almost all CBCL subscales than asthmatic children. Externalizing behavior caused significant anxiety, depressive and stress levels (p<0.05), whereas internalizing behaviors caused significant in stress level but not to anxiety and depressive levels. Conclusions: Mothers of ADHD children are more psychologically distressed. Their psychological distress is contributed mainly by externalizing behaviors of their ADHD children.